Characterization of a novel HLA‐DRB1 allele, HLA‐DRB1*13:215, in an Italian bone marrow donor. (12th September 2016) - Fornaciari, S.; Sciarrino, R.; Curcio, M.; Scatena, F.; Mariotti, M. L.
Abstract : One nucleotide substitution at residue 142 of the HLA‐DRB1*13:01:01 results in a new allele, HLA‐DRB1*13:215 .